2005
DOI: 10.1093/ps/84.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor-I gene polymorphism associations with growth, body composition, skeleton integrity, and metabolic traits in chickens

Abstract: Molecular genetic selection on individual genes is a promising method to genetically improve economically important traits in chickens. A resource population was developed to study the genetics of growth, body composition, skeletal integrity, and metabolism traits. Broiler sires were crossed to dams of 2 diverse, highly inbred lines (Leghorn and Fayoumi), and the F1 birds were intermated by dam line to produce broiler-Leghorn and broiler-Fayoumi F2 offspring. Growth, body composition, skeletal integrity, and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
4
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 34 publications
4
110
4
6
Order By: Relevance
“…Sci., 9 (4): 213-222, 2015 weights of males were higher than those of females. These results are disagree with the results of Zhou et al (2005) who indicated that IGF-I gene polymorphism was associated with growth, body composition, skeleton integrity and metabolic traits in chickens. Also, disagree with the results of Gouda and Essawy (2010) who analyzed the polymorphism of IGF-I gene among Egypt chicken breeds and indicated their effect on the growth traits of Table 3 chicken was significant.…”
Section: Broilers ---------------------------------------------------contrasting
confidence: 99%
See 3 more Smart Citations
“…Sci., 9 (4): 213-222, 2015 weights of males were higher than those of females. These results are disagree with the results of Zhou et al (2005) who indicated that IGF-I gene polymorphism was associated with growth, body composition, skeleton integrity and metabolic traits in chickens. Also, disagree with the results of Gouda and Essawy (2010) who analyzed the polymorphism of IGF-I gene among Egypt chicken breeds and indicated their effect on the growth traits of Table 3 chicken was significant.…”
Section: Broilers ---------------------------------------------------contrasting
confidence: 99%
“…Amills et al (2003) found suggestive associations (p#0.05) between IGF1-SNP and average daily gain at 107 days. Zhou et al (2005) found in the F2 generation of hybrids Leghorn×broiler Fayoum×broiler, a significant association (at 5% significance level) between IGF1-SNP and average daily gains. Some results of research on the IGF-1 gene polymorphism is associated with growth have been reported in chickens (Sco et al, 2001;Kita et al, 2005;Li et al, 2009), in sheep (Zhang et al, 2008) and in cattle (Curi et al, 2006;Siadkowska et al, 2006;Arman et al, 2012).…”
Section: Body Weight Gainmentioning
confidence: 75%
See 2 more Smart Citations
“…These studies have focused on identifying QTL responsible for body weight [39,46,47,51,52,55], feed-efficiency [57], growth [7,20,27,55,57,62], carcass characteristics [12,23,24,56], and egg traits [27,39,44,54,59]. Other researchers have investigated specific candidate genes potentially associated with variation in traits relating to bone integrity [31,61]. However, this is the first report of a genome scan focused on the identification of QTL influencing bone traits in chickens.…”
Section: Discussionmentioning
confidence: 99%